A new, peculiar genus of Cossoninae (Coleoptera, Curculionidae) from Oman with description of a new species, larva and notes on biology - Hlaváč, Peter; Skuhrovec, Jiří; Pelikán, Jan (Zootaxa, 2020)
A new genus and species of the subfamily Cossoninae, Omanocossonus sabulosus gen. et sp. nov. is described from Oman. All specimens including larvae were found on sand dunes on the seashore in roots of Calotropis procera (Aiton) W.T. Aiton. The crucial features, including male and female terminalia, are illustrated, and the taxonomic position of the new genus within Cossoninae is briefly discussed. The generic status of Lindbergius Roudier, 1957 is resurrected. The mature larva of the new species is described, larval morphology is discussed and the current state of knowledge about immature stages of Cossoninae is summarized.